2021
DOI: 10.1002/ajmg.b.32875
|View full text |Cite
|
Sign up to set email alerts
|

Investigating perceived heritability of mental health disorders and attitudes toward genetic testing in the United States, United Kingdom, and Australia

Abstract: Our beliefs about the heritability of psychiatric traits may influence how we respond to the use of genetic information in this area. In the present study, we aim to inform future education campaigns as well as genetic counseling interventions by exploring common fears and misunderstandings associated with learning about genetic predispositions for mental health disorders. We surveyed 3,646 genetic research participants from Australia, and 960 members of the public from the United Kingdom, and the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The relationship between these two items showed that those who believed that people born to parents with schizophrenic disorder are destined to develop schizophrenia themselves, despite any protective factors (such as the possibility of growing up with parents without mental disorders). In line with previous literature (e.g., Carver et al, 2017;Chapman et al, 2019;Molster et al, 2009;Morosoli et al, 2021;Willoughby et al, 2019), these results appeared to confirm that the general population tend to perceive mental disorders as heritable.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between these two items showed that those who believed that people born to parents with schizophrenic disorder are destined to develop schizophrenia themselves, despite any protective factors (such as the possibility of growing up with parents without mental disorders). In line with previous literature (e.g., Carver et al, 2017;Chapman et al, 2019;Molster et al, 2009;Morosoli et al, 2021;Willoughby et al, 2019), these results appeared to confirm that the general population tend to perceive mental disorders as heritable.…”
Section: Discussionsupporting
confidence: 91%
“…The meta-analysis included 21 new discovery samples of the BroadABC with GWAS data on a continuous measure of ASB, totaling 50,252 participants: The National Longitudinal Study of Adolescent to Adult Health [60] (ADH), Avon Longitudinal Study of Parents and Children [61][62][63], Brain Imaging Genetics [64], CoLaus|PsyCoLaus [65], Collaborative Study on the Genetics of Alcoholism [66], Finnish Twin Cohort [67] (FinnTwin), The Genetics of Sexuality and Aggression [68], Minnesota Center for Twin and Family Research [69], Phenomics and Genomics Sample [70], eight samples of the QIMR Berghofer Medical Research Institute (QIMR; 16Up project [16UP [71]], Twenty-Five and Up Study [25UP [72]], Genetics of Human Agency [73], Prospective Imaging Study of Ageing [74], Semi-Structured Assessment for the Genetics of Alcoholism SSAGA Phase 2 [SS2 [75]], Genetic Epidemiology of Pathological Gambling [GA [76]], Twin 89 Study [T89 [77]], and Nicotine Study [NC [78]]), Spit for Science [79] (S4S), two samples (from different genotype platforms) of the Twin Early Development Study [80], and the TRacking Adolescents' Individual Lives Survey [81].…”
Section: Methods Samplesmentioning
confidence: 99%
“…Understanding factors that shape attitudes towards genetic testing is an important agenda for the Genomic Era. Several studies found that people's views on genetic testing are related to their genetic literacy [18,29,30]. For example, one recent study, with more than 5400 participants from several countries, showed that willingness to undergo genetic testing was positively correlated with genetic knowledge (B = .18; [16]).…”
Section: Genetic Knowledge and Willingness To Undergo Testingmentioning
confidence: 99%